2000
DOI: 10.1073/pnas.070050797
|View full text |Cite
|
Sign up to set email alerts
|

Identification with a recombinant antibody of an inner-ear cytokeratin, a marker for hair-cell differentiation

Abstract: Extensive biochemical characterization of cells in the inner ear has been hampered by a lack of tools with which to identify inner-ear proteins. By using a single-chain antibody fragment isolated from a bacteriophage-displayed library, we have identified a cytokeratin that is abundant in nonsensory cells of the frog inner ear. Although the progenitors of hair cells exhibit strong immunoreactivity to this cytokeratin, the signal declines in immature hair cells and vanishes as the cells mature. The correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…In amphibian, avian and mammalian vestibular systems, cytokeratins are preferentially localized in supporting cells (Cyr et al, 2000;Meiteles and Raphael, 1994;Stone et al, 1996). However, unlike previous studies, we also observed weak puncta of cytokeratin labeling in hair cells, possibly In sections from explants fixed 18 h after a 6-h incubation with gentamicin, cellular extrusions ( * ) are frequently seen above the sensory epithelium.…”
Section: Cytokeratinscontrasting
confidence: 83%
See 1 more Smart Citation
“…In amphibian, avian and mammalian vestibular systems, cytokeratins are preferentially localized in supporting cells (Cyr et al, 2000;Meiteles and Raphael, 1994;Stone et al, 1996). However, unlike previous studies, we also observed weak puncta of cytokeratin labeling in hair cells, possibly In sections from explants fixed 18 h after a 6-h incubation with gentamicin, cellular extrusions ( * ) are frequently seen above the sensory epithelium.…”
Section: Cytokeratinscontrasting
confidence: 83%
“…Cytokeratin expression is down regulated during hair cell differentiation (Cyr et al, 2000;Raphael et al, 1987). The upregulation of cytokeratins in hair cell extrusions indicates the epithelial origin of these sensory cells, and associated apoptotic cell death mechanisms (Caulin et al, 1997;Leers et al, 1999).…”
Section: Cytokeratinsmentioning
confidence: 99%
“…After fixation, these cultures were labeled with phalloidin, a marker of filamentous actin, and immunolabeled with antisera against myosin VI, a known HC marker (84), and a single-chain antibody fragment against a novel cytokeratin expressed in bullfrog SCs (85). The morphology, ultrastructure, and immunolabeling of cells in these cultures were then examined with confocal and transmission electron microscopy.…”
Section: Morphology and Immunoreactivity In Mbc Culturesmentioning
confidence: 99%
“…Merkel cells express K8, K18 and K19 (Moll et al 1984;Narisawa et al 1994;Larouche et al 2008), and smooth muscle cells in the human placenta cross-react with an anti-K8 antibody, thus indicating that they contain K8 (Miettinen & Fetsch, 2000) or at least a molecule with an epitope that binds to this antibody. Similarly, in the transition from a non-sensory to a specialized sensory cell, the synthesis of keratins is downregulated (Cyr et al 2000).…”
Section: Keratins In Epithelial Cells With Special Functionsmentioning
confidence: 99%